2022
DOI: 10.1016/j.cub.2021.10.049
|View full text |Cite
|
Sign up to set email alerts
|

Aurora B phosphorylates Bub1 to promote spindle assembly checkpoint signaling

Abstract: Aurora B phosphorylates Bub1 to promote spindle assembly checkpoint signaling Highlights d Aurora B cannot activate the SAC because it cannot phosphorylate Knl1 ''MELT'' motifs d Aurora B promotes SAC signaling by phosphorylating Bub1 d Aurora B activity promotes Mad1 recruitment via Bub1

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 71 publications
1
24
0
Order By: Relevance
“…However, BubR1 is unlikely to be recruited to budding yeast kinetochores ( Tromer et al. , 2016 ; Roy et al. , 2022 ), and in nocodazole-treated HeLa cells, the disruption of Bub1-mediated BubR1 recruitment slightly strengthens the SAC ( Overlack et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, BubR1 is unlikely to be recruited to budding yeast kinetochores ( Tromer et al. , 2016 ; Roy et al. , 2022 ), and in nocodazole-treated HeLa cells, the disruption of Bub1-mediated BubR1 recruitment slightly strengthens the SAC ( Overlack et al.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the extended mitosis was due to increased Mad2-Cdc20 and MCC formation in HeLa cells and fission yeast ( Leontiou et al. , 2019 ; Roy et al. , 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Whether Aurora B activates mitotic checkpoint signaling solely by releasing inappropriate attachments to produce unattached kinetochores during error correction or participates directly in checkpoint signaling has been debated in the field. However, on balance, recent evidence favors the conclusion that Aurora B functions in mitotic checkpoint signaling independent of error correction in multiple species ( Kallio et al, 2002 ; Petersen and Hagan, 2003 ; Vader et al, 2007 ; Santaguida et al, 2011 ; Hadders et al, 2020 ; Roy et al, 2022 ). Our evidence supports this conclusion, and demonstrates that increased Aurora B, which reduces Aurora B substrate phosphorylation, also weakens mitotic checkpoint signaling in response to unattached kinetochores.…”
Section: Discussionmentioning
confidence: 98%
“…Early work reported that Aurora B was necessary to activate the mitotic checkpoint in response to lack of tension caused by taxol, but not in response to unattached kinetochores caused by loss of microtubules ( Biggins et al, 1999 ; Biggins and Murray, 2001 ; Carvalho et al, 2003 ; Pinsky et al, 2006 ). However, others have reported that Aurora B also functions directly in mitotic checkpoint activation, even in the absence of microtubules, and contributes to formation of mitotic checkpoint complexes ( Santaguida et al, 2011 ; Matson et al, 2012 ; Matson and Stukenberg, 2014 ; Hadders et al, 2020 ; Roy et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that CDC20 promotes several types of cancer progression, including glioma and lung cancer ( Wang et al, 2013 ; Wang et al, 2015 ). Aurora B phosphorylates BUB1 to facilitate spindle assembly checkpoint signaling, and target Aurora B kinase can prevent and overcome resistance to EGFR inhibitors in lung cancer ( Tanaka et al, 2021 ; Roy et al, 2022 ). KIF11, known as mitotic spindle-specific protein, and its oral inhibitor 4SC-205 demonstrates anti-tumor activity and enhances targeted therapy in primary and metastatic neuroblastoma models ( Masanas et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%